Program Erasmus a internacjonalizacja studiów - Walesiak, Marta (Internationalization of Studies with the Erasmus Programme, 2009)
The paper presents priorities of the Erasmus Programme policy in EU countries and its international dimension. The history of the programme, its goals and connection with the Bologna Process are discussed. In the fundamental part of the paper, the co-operation between countries which are taking part in this programme (Poland is also taken into consideration) is presented. The paper discusses both the advantages and disadvantages of the Erasmus Programme and shows its growing possibilities.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 86, s. 104-113